Depression and Anxiety Related to Adult Development of University Loan Fund Students During Covid - Anusaksathien, Kantabhat (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 3 (2024): July - September 2024DO - 10.14456/jcdr-hs.2024.19, 2024)
The study focused on vulnerable students with loan funds during the coronavirus pandemic. The first research objective is to assess levels of adult development anxiety and depression and the second is to study the relationship of Naresuan University students with student loans during the coronavirus outbreak. A sample of 400 student loan fund students were given the developmental anxiety to adulthood assessment form (AAA-NU) and the depression test (PHQ-9). Quantitative data were analyzed by One-Way ANOVA and t-test statistical methods and results showed that most of the student loan fund students had anxiety about developing into adulthood at a relatively low level related to factors of anxiety in all four areas of work, occupation, adaptation and situational, and most of them had mild depression. Quantitative data analysis revealed statistically significant differences among the university faculty with anxiety in developing into adulthood at the .05 level. A Pearson correlation analysis indicated the level of anxiety and of depression were positively correlated significantly at a moderate level, r = .627, p < .001. Keywords: Anxiety Related to Adult Development, Depression, Student Loans Fund, Covid